Television Drama in Spain and Latin America : Genre and Format Translation - Julian Smith, Paul (Institute of Modern Languages Research, 2020)
Television Drama in Spain and Latin America addresses two major topics within current cultural, media, and television studies: the question of fictional genres and that of transnational circulation. While much research has been carried out on both TV formats and remakes in the English-speaking world, almost nothing has been published on the huge and dynamic Spanish-speaking sector. This book discusses and analyses series since 2000 from Spain (in both Spanish and Catalan), Mexico, Venezuela, and (to a lesser extent) the US, employing both empirical research on production and distribution and textual analysis of content. The three genres examined are horror, biographical series, and sports-themed dramas; the three examples of format remakes are of a period mystery (Spain, Mexico), a romantic comedy (Venezuela, US), and a historical epic (Catalonia, Spain). Paul Julian Smith is Distinguished Professor at the Graduate Center, City University of New York. He was previously Professor of Spanish at the University of Cambridge. He is the author of twenty books and one hundred academic articles.
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); Venezuela (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Transnational Latin American Television: Genres, Formats and Adaptations - Ribke, Nahuel (Routledge, 2020)
This book examines the process of transnationalization of Latin American television industries. Drawing upon six representative case studies spanning the subcontinent’s vast and diverse geo-political and cultural landscape, the book offers a unique exploration of the ongoing formation of interrelated cultural, technological, and political landscapes, from the mid-1980s to the present. The chapters analyse the international circulation of the genres and formats of entertainment television across the subcontinent to explore the main driving forces propelling the production and consumption of television contents in the region, and what we can learn about the cultural and social identities of Latin American audiences following the journey of genres, formats, and media personalities beyond their own national borders. Taking a contemporary interdisciplinary approach to the study of transnational television industries, this book will be of significant interest to scholars and students of television and film studies, communication studies, Latin American studies, global media studies, and media and cultural industries.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Asie (lieu de production du savoir); Israël (lieu de production du savoir); _Nettoyé

Telenovelas in Brazil: From Traveling Scripts to a Genre and Proto-Format both National and Transnational - Straubhaar, Joseph (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, we argue that there are several layers of genre, proto-format commercialization of program elements, and current commercially licensed formats. Some genre traditions, like melodrama, tend to be large, over-arching categories that already have a long history before television (Martín-Barbero 1993). Speciﬁc genres of television production, like the U.S. soap opera or the Latin American telenovela can develop within that larger tradition. Even more speciﬁc genres, like the Brazilian socially engaged or historical telenovelas, versus the romantic Mexican Cinderella story telenovela (Hernandez 2001), develop or emerge over time within those genre traditions. Television formats are now often distinguished as a parallel category which looks at forms of television that are packaged for licensing, transfer across cultures, and localized adaptation or implementation by regional, national or local networks. Speciﬁc formats are often imported and adopted. They can feed into genre development, grafted on to older traditions.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Examining Professional and Academic Culture in Chilean Journalism and Mass Communication Education - Mellado, Claudia (Journalism Studies, 2011)
This article discusses key findings from a survey of the professional patterns, scholarly productivity, and educational characteristics of Chilean Journalism and Mass Communication (JMC) educators, as well as documentary information about the schools where they work. The results reveal a weak academic culture that contrasts with a strong professional culture among the members of this community, but also the influence that both organizational and individual variables have on Chilean JMC educators' orientations. Specifically, the analyses indicated that the level of education, part-time/full-time commitment, and the type of university are the most influential factors in defining both the prevalence of a professional culture and the lack of research productivity. These findings support other international studies, indicating a global tendency across key variables that influence academic development in the field. Likewise, it shows how distant Chilean JCM educators are from the university-scholarly tradition.
Keywords: 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Procesos de invención decoloniales sobre visualidades indígenas. Hacia una reconfiguración de los imaginarios hegemónicos en el nordeste argentino - Reyero, Alejandra; Navas, Maia (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
El objetivo del artículo es discutir la potencialidad de prácticas artísticas contemporáneas que plantean ejercicios decoloniales al desestabilizar las matrices perceptivas eurocéntricas sobre grupos étnicos latinoamericanos. Desde la perspectiva de los estudios visuales, aborda la tentativa de demolición crítica de la cultura visual y los regímenes de visibilidad regidos por la lógica de la hipercomunicación y las tecnologías digitales. El punto de partida es el análisis del videoensayo Ashipegaxanacxanec iniciado en 2020 a partir de las acciones de control implementadas en la pandemia de covid-19. La producción se inscribe en las líneas de investigación del Núcleo de Estudios y Documentación de la Imagen (Nedim), Conicet-UNNE, con la finalidad de resignificar el acervo fotográfico del antropólogo alemán Lehmann Nitsche obtenido en el contexto de la masacre indígena en la Reducción de Napalpí, Chaco, en 1924. Metodológicamente, la propuesta explora la configuración experiencial de visualidades expandidas en la escena contemporánea, a partir de un anclaje en la dimensión especulativa en sintonía con un acercamiento contextual situado en las relaciones de convergencia entre pro- cedimientos, materiales, formatos, dispositivos e instancias disruptivas de prácticas y trayectorias estéticas. Ello supone la activación de procesos heurísticos y poéticos mediados por el ensayo y la escritura como montaje. Propuestas como el videoensayo analizado instauran la pregunta por el archivo y la memoria a través del montaje de temporalidades contradictorias. Su lugar de enunciación se posiciona como posibilidad de insurgencia estética que clausura tentativas de exotización hegemónica por parte de los dispositivos de control contemporáneos. The goal of this paper is to discuss the potentiality of contemporary artistic prac-tices that propose decolonial exercises by destabilizing the Eurocentric perceptual matrices on Latin American ethnic groups. From the perspective of visual studies, it addresses the attempt to critically demolish visual culture and the regimes of visibility governed by the logic of hypercommunication and digital technologies. The starting point is the analysis of the Ashipegaxanacxanec video essay started in 2020 based on the control actions implemented in the COVID-19 pandemic. The production is part of the research of the Image Studies and Documentation Center (Nedim), Conicet-UNNE, with the purpose of redefining the photographic collection of German anthropologist Lehmann Nitsche, obtained in the context of the indigenous massacre in the Napalpí reduction in Chaco, in 1924. Methodologi-cally, the proposal explores the experiential configuration of expanded visualities in the contemporary scene, based on an anchoring in the speculative dimension in tune with a contextual approach in the convergence relationships between proce-dures, materials, formats, devices and disruptive instances of practices and aes-thetic trajectories. This supposes the activation of heuristic and poetic processes mediated by essays and writing as montage. Proposals such as the analyzed video essay establish the question about the archive and memory through the montage of contradictory temporalities. Its place of enunciation is positioned as a possibili-ty of aesthetic insurgency that closes any attempts at hegemonic exoticization by contemporary control devices
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Cultural code: video games and Latin America - Penix-Tadsen, Phillip (The MIT Press, 2016)
How culture uses games and how games use culture: an examination of Latin America's gaming practices and the representation of the region's cultures in games. Video games are becoming an ever more ubiquitous element of daily life, played by millions on devices that range from smart phones to desktop computers. An examination of this phenomenon reveals that video games are increasingly being converted into cultural currency. For video game designers, culture is a resource that can be incorporated into games; for players, local gaming practices and specific social contexts can affect their playing experiences. In Cultural Code, Phillip Penix-Tadsen shows how culture uses games and how games use culture, looking at examples related to Latin America. Both static code and subjective play have been shown to contribute to the meaning of games; Penix-Tadsen introduces culture as a third level of creating meaning. Penix-Tadsen focuses first on how culture uses games, looking at the diverse practices of play in Latin America, the ideological and intellectual uses of games, and the creative and economic possibilities opened up by video games in Latin America—the evolution of regional game design and development. Examining how games use culture, Penix-Tadsen discusses in-game cultural representations of Latin America in a range of popular titles (pointing out, for example, appearances of Rio de Janeiro's Christ the Redeemer statue in games from Call of Duty to the tourism-promoting Brasil Quest). He analyzes this through semiotics, the signifying systems of video games and the specific signifiers of Latin American culture; space, how culture is incorporated into different types of game environments; and simulation, the ways that cultural meaning is conveyed procedurally and algorithmically through gameplay mechanics. Source: Publisher
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé